Syncope Unit: rationale and requirement - the European Heart Rhythm Association position statement endorsed by the Heart Rhythm Society - Kenny, Rose; Doherty, Colin; Mc Mahon, Christine (My University, 2015)
The European Society of Cardiology (ESC) has played an important role in advancing our understanding of the causes, optimal investigation, and management of syncope through publication of practice guidelines in 2001, 2004, and 2009.1–3 The 2009 ESC guidelines recommend the establishment of formal Syncope Units (SUs)—either virtual or physical site within a hospital or clinic facility—with access to syncope specialists and specialized equipment.3 In response, this position statement by the European Heart Rhythm Association (EHRA) endorsed by the Heart Rhythm Society (HRS) offers a pragmatic approach to the rationale and requirement for an SU, based on specialist consensus, existing practice and scientific evidence (see Appendix). The panel consists of specialists who have experience in developing and leading such units representing cardiology, geriatric and general internal medicine, neurology, and emergency medicine. This document is addressed to physicians and others in administration, who are interested in establishing an SU in their hospital, so that they can meet the standards proposed by ESC-EHRA-HRS
PUBLISHED
Keywords: Faint; Fall; Neurocardiogenic syncope; Seizure; Syncope; Syncope Unit; Transient loss of consciousness; Faint; Fall; Neurocardiogenic syncope; Seizure; Syncope; Syncope Unit; Transient loss of consciousness; Ageing